Tafsir Ayat-Ayat Gender dalam Al-Qur’an dengan Pendekatan Ekofeminisme: Kritik Terhadap Tafsir Feminisme Liberal - Mintaraga Eman Surya (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
The interpretation of the gender verses in the Al-Qur'an with eco-feminism approach is the criticism and alternative interpretation of gender verses with liberal feminism approach. This is because of the liberal feminism puts men and women in the positions of binary opposition that makes competition and rivalry. The purposes of this paper are to determine the composition of the interpretation of the gender verses in the Al- Qur'an with eco-feminism approach and to know the function and the position of the interpretation of gender verses with eco-feminism approach as a criticism and an alternative interpretation of gender verses with liberal feminism approach. This paper is expected to be an alternative of the interpretation of liberal feminism which becomes mainstream in Islamic studies and gender.